Rusia y la anexión de Crimea o la crisis de la post Guerra Fría - Salmón, Elizabeth (2014)
The prohibition of the threat or use of force is part of the structural principles of contemporary international law. As a corollary to this norm, no state may violate the territorial integrity of the other one. However, one of the most recent issues that has sparked intense debate has been the fact that the Russian Federation annexed Crimea in March 2014. In this context, the present article examines how Russia’s action is contrary to article 2, paragraph 4 of the United Nations Charter, despite the arguments made by its authorities. It also evaluates if this situation creates an obligation of non- recognition for other members of the international community. Finally, we will discuss the potential impact of this event on the future development of international law relating to international peace and security.